Extravasation of Pt-based chemotherapeutics – bioimaging of their distribution in resectates using laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS)1. Issue 3 (11th March 2015) - Egger, Alexander E.; Kornauth, Christoph; Haslik, Werner; Hann, Stephan; Theiner, Sarah; Bayer, Günther; Hartinger, Christian G.; Keppler, Bernhard K.; Pluschnig, Ursula; Mader, Robert M.
<x xml:space="preserve">Abstract</x> Spatially resolved quantification of platinum distribution in patients that exhibited extravasation was feasible up to 4 weeks upon drug application.